The influence of work pressure, safety climate and safety participation in determining safety behaviour among local and foreign workers in a Malaysian steel industry - Sathia Segaran, Nadesan (2013)
This study was conducted to determine the factors which influence safety behaviour among workers at a Malaysian steel industry. The significance of this study is explained by the fact that the country is experiencing a surge in foreign workers which could detrimentally affect the overall safety behaviour of employees. A total of 160 questionnaires’ were distributed to the workers in a metal stamping industry. The questionnaire encompasses 3 independent variables of safety climate, safety participation, perceived work pressure and a dependent variable which is represented by safety behaviour. Results from this research shows that safety behaviour is positively correlated with safety participation and safety climate, and negatively correlated with work pressure. Workers who are working in morning shifts have been found to possess better safety participation, an increase in perceived work pressure, a better perception of safety climate and safety behaviour. Comparison between the Malaysian work force and foreign workers showed that Malaysian workers possess better safety behaviour, an elevated perceived safety climate and good safety participation compared to their foreign counterparts. In addition, workers with an education level below primary school lack safety participation. In another note, better safety participation was reported among employees with higher academic qualifications. Multiple regression analyses were performed to predict the safety behaviour of workers with respect to safety climate, safety participation and perceived work pressure. The results of the regression analyses suggest that safety climate and safety participation were more predictive and accounted for more unique variance in the safety behaviour variables than perceived safety pressure. Future researches are worth extended to include high risk metal and steel industry